Biomass-based integrated gasification combined cycle with post-combustion CO2 recovery by potassium carbonate: Techno-economic and environmental analysis. (6th April 2020) - Ghiat, Ikhlas; AlNouss, Ahmed; McKay, Gordon; Al-Ansari, Tareq
Highlights: A biomass based integrated gasification combined cycle (BIGCC) with post combustion carbon capture is modeled and simulated using Aspen Plus. Chemical absorption using Piperazine promoted potassium carbonate is investigated to remove CO2 from the exhaust gas of the BIGCC. The integrated combined system is studied using a thermodynamic equilibrium model for the BIGCC and a rate-based model for the carbon capture unit. A techno-economic and environmental analysis is conducted to assess the overall integrated system. Abstract: In this study, a thermodynamic model depicting integrated bioenergy with carbon capture and storage (BECCS) system is developed using Aspen Plus under thermodynamic equilibrium for the power generation segment, and a rate-based model for the carbon capture segment representing CO2 recovery from the exhaust flue of a biomass based integrated gasification combined cycle (BIGCC). A thorough techno-economic analysis is conducted for the integrated system to evaluate system-wide environmental impacts and economic costs. The carbon capture is modeled using post combustion technology with chemical absorption by means of Piperazine promoted potassium carbonate to absorb the CO2 from the exhaust stream of the gas turbine. The results demonstrate that the proposed system with 80% carbon capture has negative emissions of -0.31 kg/kWh of CO2 -e, when assuming neutral emissions from the BIGCC. For a production of 419 kW of net electricity, the overall energy and exergy efficiencies are 43.8% and 57.2%, respectively.